Do Strict Capital Requirements Raise the Cost of Capital? Bank Regulation, Capital Structure, and the Low-Risk Anomaly - Baker, Malcolm; Wurgler, Jeffrey (American Economic Review, 2015)
Traditional capital structure theory predicts that reducing banks' leverage reduces the risk and cost of equity but does not change the weighted average cost of capital, and thus the rates for borrowers. We confirm that the equity of better-capitalized banks has lower beta and idiosyncratic risk. However, over the last 40 years, lower risk banks have not had lower costs of equity (lower stock returns), consistent with a stock market anomaly previously documented in other samples. A calibration suggests that a binding ten percentage point increase in Tier 1 capital to risk-weighted assets could double banks' risk premia over Treasury bills.